Recurrent venous thromboembolism in patients with pulmonary embolism and right ventricular dysfunction: a post-hoc analysis of the Hokusai-VTE study. Issue 9 (September 2016) - Brekelmans, Marjolein P A; Ageno, Walter; Beenen, Ludo F; Brenner, Benjamin; Buller, Harry R; Chen, Cathy Z; Cohen, Alexander T; Grosso, Michael A; Meyer, Guy; Raskob, Gary; Segers, Annelise; Vanassche, Thomas; et al.
Summary: Background: In patients with pulmonary embolism, right ventricular dysfunction is associated with early mortality. The Hokusai-VTE study used N-terminal pro-brain natriuretic peptide (NT-proBNP) and right to left ventricular diameter ratio on CT as indicators of right ventricular dysfunction and reported that recurrent venous thromboembolism rates were lower with edoxaban than warfarin. The aim of the current study was to further explore the significance of right ventricular dysfunction and investigate potential explanations for the superiority of edoxaban—ie, differences in baseline clinical characteristics, duration of initial heparin treatment, bleeding rates, or quality of warfarin treatment. Methods: The Hokusai-VTE trial was a randomised, double-blind, event-driven non-inferiority trial in patients from centres in 37 countries that compared edoxaban with warfarin in the treatment of acute venous thromboembolism. Patients received treatment for at least 3 months and up to a maximum of 12 months. Patients were followed up for 12 months. Outcome data at 12 months was collected for all patients irrespective of treatment duration. This prespecified subgroup analysis focuses on the included patients with pulmonary embolism. The primary efficacy outcome was the incidence of adjudicated symptomatic recurrent venous thromboembolism defined as a composite of deep vein thrombosis or non-fatal or fatal pulmonary embolism at 12 months. Recurrence rates with edoxaban and warfarin were compared in patients with and without right ventricular dysfunction. In those with NT-proBNP concentrations of 500 pg/mL or higher, we compared baseline characteristics, duration of heparin treatment, and bleeding leading to study drug discontinuation in the edoxaban and warfarin groups. We also assessed quality of warfarin treatment. All analyses were done with the modified intention-to-treat population. The Hokusai-VTE trial is registered withClinicalTrials.gov, numberNCT00986154 . Findings: Between Jan 28, 2010, and Oct 5, 2012, 8292 patients were enrolled from 439 centres, of whom 8240 received at least one dose of study drug. 3319 patients had pulmonary embolism. NT-proBNP was 500 pg/mL or higher in 465 (30%) of 1565 patients given edoxaban and in 507 (32%) of 1599 given warfarin. Recurrent venous thromboembolism occurred in 14 (3%) of 465 patients in the edoxaban group and 30 (6%) of 507 in the warfarin group (hazard ratio [HR] 0·50, 95% CI 0·26–0·94; p=0·033). The right to left ventricular diameter ratio was 0·9 or higher in 414 (44%) of 937 patients in the edoxaban group and 427 (45%) of 946 in the warfarin group. Recurrent venous thromboembolism occurred in 11 (3%) of 414 and 20 (5%) of 427 patients in the edoxaban and warfarin groups (HR 0·57, 95% CI 0·27–1·17; p=0·13). Baseline characteristics, duration of heparin treatment, and rates of bleeding leading to study drug discontinuation were similar in the edoxaban and warfarin groups and the quality of warfarin management was adequate for patients with NT-proBNP concentrations of 500 pg/mL or higher. Interpretation: Findings from our analysis suggest that edoxaban is more effective than warfarin in the treatment and prevention of recurrent venous thromboembolism in patients with pulmonary embolism and evidence of right ventricular dysfunction. Funding: Daiichi Sankyo.